2019
DOI: 10.21037/atm.2019.11.118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and pathways related to atherosclerosis comorbidity and depressive behavior via RNA-seq and bioinformation analysis in ApoE−/− mice

Abstract: Background: Depression is an independent risk factor for atherosclerosis (AS), which can increase the risk of death and disability from AS. However, the mechanism of AS comorbidity with depression is complex.Methods: ApoE −/− and C57BL/6J mice were fed with a high-fat diet (model group, N=12 ♂) and a normal diet (control group, N=12 ♂). During the 15-week experimental period, the following tests were performed: coat color score, body weight, and sucrose preference tests (every 2 weeks); open-field test (1 st ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In our published paper, we demonstrated that ApoE −/− mice with a high-fat diet accelerated the formation of atherosclerosis and depression-like behavior changes. RNA-seq combined with bioinformatics analysis showed that inflammatory chemokine genes and related pathways are highly expressed in the prefrontal cortex and hippocampus regions of the atherosclerosis co-depression mice, but the detailed mechanisms affecting these genes and pathways need to be further studied ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our published paper, we demonstrated that ApoE −/− mice with a high-fat diet accelerated the formation of atherosclerosis and depression-like behavior changes. RNA-seq combined with bioinformatics analysis showed that inflammatory chemokine genes and related pathways are highly expressed in the prefrontal cortex and hippocampus regions of the atherosclerosis co-depression mice, but the detailed mechanisms affecting these genes and pathways need to be further studied ( Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aorta was opened lengthwise and the edges and corners were flattened on black boards. The en face analysis of the lesion area on the whole aorta was quantified based on Oil Red O staining, using Image-Pro Plus 6.0 software (Media Cybernetics, Bethesda, USA) [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depression is a mental illness associated with depressed mood, loss of interest, and energy fatigue ( Zhou et al, 2019 ). Not only it causes serious damage to the patients but also imposes a huge economic burden on society due to its high morbidity rate and recurrence rate ( Jun et al, 2014 ; Can et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%